ORGANIZATIONAL BEHAVIOR AND ITS INFLUENCE ON EMPLOYEE LOYALTY AT WAJIR SEAFOOD - Remigius Obortus Laia; Erika Hulu; Angel Aritonang; Farming Vica; Gina Sonia Symbol; Bayu Teta (CV Naskah Aceh, 2025)
The purpose of this scientific research is to examine how organizational behavior (including leadership, communication, and work culture) impacts employee loyalty at Wajir Seafood, Medan. This study employs a census approach as its quantitative research method, involving a sample of 50 employees. Data was gathered through questionnaires and analyzed using simple linear regression with SPSS Version 22. The findings reveal that organizational behavior significantly affects employee loyalty (β = 0. 351, p = 0. 001), showing a moderate correlation (R = 0. 437) and a contribution of 19. 1% (R² = 0. 191). These results align with the theories proposed by Robbins (2002) and Luthans (2011), highlighting the necessity of a supportive work environment. However, 80. 9% of other factors, such as compensation and training, have not been investigated in this model. The study concludes that enhancing organizational behavior could be a preliminary strategy for fostering employee loyalty, although it should be supplemented by additional interventions. Practical implications include enhancing internal communication, recognition systems, and training programs for better outcomes.